Sources of brand equity in a government programme: a case of the renewable energy independent power producers programme (REIPPP) in South Africa - Mojanaga, Nonesi Desiree (My University, 2020)
Assessing the sources of brand equity in the government sector is an area of limited research. This research report applies the Brand Equity theoretical model developed by Aaker (1991a; 1991b) to determine the sources of brand equity in a public sector energy programme in South Africa. The Renewable Energy Independent Power Producers Programme (REIPPP) is a private-public partnership in the renewable energy sector, introduced in 2010. A brand is considered to be one of the most important intangible assets of any organisation, and therefore the determination of the sources of its value, or brand equity, is of great importance. A quantitative research approach was adopted to guide the study, using a structured survey questionnaire. Data was collected through an online survey from a sample of thirty-two respondents, most of whom have been extensively involved in the REIPPP and analysed using descriptive and inferential statistical methods. The results of the research study highlighted the most important factors affecting brand equity in the REIPPP, which are brand awareness and perceived benefit. The findings show that Aaker’s (1991a; 1991b) Brand Equity model has relevance and applicability in the public sector. The contribution of this report is to enhance academic understanding of brand equity in the public sector and to explore the implications for management practice whilst providing marketers in the public sector with the tools for public sector marketing
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Brand equity; Public sector; Renewable energy; UCTD; SDG-7: Affordable and clean energy; SDG-8: Decent work and economic growth